Fusion of a Tooth with a Supernumerary Tooth: A Case Report and Literature Review of 35 Cases - Tatsuya Akitomo; Satoru Kusaka; Momoko Usuda; Mariko Kametani; Ami Kaneki; Taku Nishimura; Masashi Ogawa; Chieko Mitsuhata; Ryota Nomura (Children, 2023)
Tooth fusion is a dental anomaly with a prevalence of 0.1% in permanent dentition. The aim of this paper is to present the occurrence, region of fusion, and prognosis of fused tooth which is a very rare case in the literature. The authors present a very rare case with a maxillary right lateral incisor fused to a supernumerary tooth on the palatal side. The eruption was delayed, but eruption occurred naturally at 9 years and 6 months. However, cone-beam computed tomography at 11 years and 6 months revealed it was diagnosed as a fused tooth. The authors undertook a literature review over the past 10 years and found 30 articles about fused teeth between permanent teeth and supernumerary teeth. It was more common in males than females and there were no differences depending on the occurrence. Mesiodistal fusion was more common in the incisor region, while labiopalatal fusion was more common in the molar region. Most cases required dental treatment with a surgical approach, root canal treatment, or orthodontic treatment. The present study highlights the importance of long-term follow-up and suggests the region of fusion and prognosis of the fused tooth may vary depending on the occurrence.